Analysis Of Business Feasibility Study Of Msme Bakso Bakar Dang In Manna, South Bengkulu - Tharisa Qhumayira; Neri Susanti; Iswidana Utama Putra (Journal of Management, Economic, and Accounting, 2026)
The purpose of this study is to determine the financial feasibility of the Bakso Bakar Dang MSME business in Manna, South Bengkulu based on the results of the Business Feasibility Study Analysis from the financial aspect. Using the Net Present Value (NPV), Internal Rate of Return (IRR), Payback Period (PP), and Profitability Index (PI) methods. The type of research used in this study is descriptive research with a quantitative approach. The results show that the NPV value is Rp. 538.315.934 (positive), the IRR reaches 38,14%, the PP value in 2023 is 4,1 months and in 2024 increases to 4,4 months indicating that the investment capital of Rp. 138.652.000 can be returned in a short time and the PI value is 2,92. Based on these results, it can be concluded that the Bakso Bakar Dang MSME is feasible to run and has the potential for high financial profits.